2021
DOI: 10.1021/acs.inorgchem.1c00159
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedrally Coordinated sp3-Hybridized Carbon in Sr2CO4 Orthocarbonate at Ambient Conditions

Abstract: We have synthesized the orthocarbonate Sr2CO4, in which carbon is tetrahedrally coordinated by four oxygen atoms, at moderately high pressures [20(1) GPa] and high temperatures (≈3500 K) in a diamond anvil cell by reacting a SrCO3 single crystal with SrO powder. We show by synchrotron powder X-ray diffraction, Raman spectroscopy, and density functional thoery calculations that this phase, and hence sp3-hybridized carbon in a CO4 4– group, can be recovered at ambient conditions. The C–O bond distances are all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 23 publications
5
39
0
1
Order By: Relevance
“…The experimental work performed by Spahr and co-authors, who appeared after this manuscript’s submission, provides unambiguous confirmation of the unexpected fact of dynamic stability of sp 3 orthocarboantes at ambient pressure.…”
Section: Discussionsupporting
confidence: 52%
“…The experimental work performed by Spahr and co-authors, who appeared after this manuscript’s submission, provides unambiguous confirmation of the unexpected fact of dynamic stability of sp 3 orthocarboantes at ambient pressure.…”
Section: Discussionsupporting
confidence: 52%
“…Calculations in which a low spin state was imposed gave too small lattice parameters, which differed markedly from the experimental values. Similar to recent results on other carbonates in which the carbon is fourfold coordinated by oxygen [24,25], the DFT calculations show that all C-O bonds are covalent, with bond populations ranging from 0.8-0.6 e − /Å 3 . The carbon atoms are therefore tetrahedrally coordinated by oxygen and thus sp 3 hybridized.…”
Section: Computational Resultssupporting
confidence: 84%
“…These investigations allowed us to derive an understanding of pressure-induced structural phase transitions and changes in the structure-property relations and the electronic state, depending on thermodynamic conditions and composition [7][8][9][10][11][12][13][14][15]. Only recently has it been shown that carbonates in which carbon is tetrahedrally coordinated by oxygen atoms, i.e., sp 3 -hybridized carbon, are stable at high pressures [16][17][18][19][20][21][22][23][24][25]. Specifically, at conditions prevalent in the deeper mantle with pressures >50 GPa, siderite (FeCO 3 ) transforms via self-oxidation-reduction reactions into new phases containing sp 3 carbon [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…28 In addition to the established orthoanions, it was recently predicted and experimentally shown that carbonates with [CO 4 ] 4− groups may even be recovered at ambient conditions. 21,25 Further, stable structures with stoichiometries M 2 [CO 4 ] and M 3 [CO 4 ]O (M = Mg, Ca, Sr, and Ba) have been predicted by DFT-based calculations. 22−25 Here, we report the successful outcome of the synthesis of one of these structures using M = Sr.…”
mentioning
confidence: 93%